Dipeptidyl peptidase‐4 inhibitors and the risk of community‐acquired pneumonia in patients with type 2 diabetes. Issue 4 (3rd February 2015) - Faillie, J.‐L.; Filion, K. B.; Patenaude, V.; Ernst, P.; Azoulay, L.
<x xml:space="preserve">Abstract</x> Aims To determine whether the use of dipeptidyl peptidase‐4 (DPP‐4) inhibitors is associated with an increased risk of community‐acquired pneumonia. Methods The UK Clinical Practice Research Datalink and the Hospital Episodes Statistics database were used to conduct a nested case–control analysis within a cohort of new users of antidiabetic drugs between 2007 and 2012. Incident cases of hospitalization for community‐acquired pneumonia were matched with up to 20 controls on age, duration of treated diabetes, calendar year and duration of follow‐up. Conditional logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for hospitalization for community‐acquired pneumonia associated with current use of DPP‐4 inhibitors compared with current use of two or more oral antidiabetic drugs. Results The cohort included 49 653 patients, of whom 562 were hospitalized for community‐acquired pneumonia during follow‐up (incidence rate 5.2/1000 person‐years). Compared with current use of two or more oral antidiabetic drugs, current use of DPP‐4 inhibitors was not associated with an increased risk of hospitalized community‐acquired pneumonia overall (adjusted OR 0.80, 95% CI 0.50–1.29) or according to duration of use (p for trend = 0.57). Conclusions The use of DPP‐4 inhibitors was not associated with an increased risk of hospitalization for community‐acquired pneumonia. Additional research is needed to assess the association between these drugs and other serious infections.